Impact of Dalteparin Sodium and Luteal Phase Support on Serum Markers, Interleukins, and Pregnancy Outcomes in Patients with In Vitro Fertilization Failure - Lei, Jinmei (Journal of Medical Biochemistry, 2025)
Introduction: In vitro fertilization-embryo transfer (IVF-ET) remains a challenging treatment for infertility, particularly in patients with repeated implantation failures. Dalteparin sodium (DS), a low molecular weight heparin, has shown promise in improving IVF outcomes due to its antithrombotic and immunomodulatory properties. This study investigated the effects of DS combined with luteal phase support (LPS) on serum markers, interleukins, and pregnancy outcomes in patients with a history of repeated IVF failure. Materials and Methods: This retrospective study included 80 patients with a history of repeated IVF failure who underwent assisted reproduction at our center. Patients were randomly assigned to receive either LPS alone (Ctrl group, n=40) or LPS combined with daily subcutaneous injections of DS (Exp group, n=40). Serum levels of β-hCG, FSH, E2, LH, CA-125, and interleukin-6 (IL-6) were measured and compared between the groups. Results: The Exp group demonstrated significantly higher clinical pregnancy rates (CPR) and embryo implantation rates (EIR) compared to the Ctrl group (P<0.05). Additionally, the miscarriage rate (MCR) was significantly lower in the Exp group (P<0.05). Moreover, the Exp group exhibited significantly lower serum levels of CA-125 and IL-6 compared to the Ctrl group (P<0.05). Improvements in quality of life (QOL) measures were also observed in the Exp group, with significant increases in physiological function, physiological role, social function, emotional function, and mental health (P<0.05). No significant difference in the incidence of adverse reactions (ARs) was found between the two groups (P>0.05). Conclusion: The combination of LPS and DS appears to be a safe and effective strategy for improving pregnancy outcomes and QOL in patients with repeated IVF failure. This combined treatment may exert its beneficial effects by modulating key serum markers and interleukins, such as CA-125 and IL-6, involved in implantation and pregnancy maintenance.